Decent Work Based on Psychology of Working Theory: Literature Review and Research Prospects - Jiang, Lena (Transactions on Social Science, Education and Humanities Research, 2024)
Decent work is of great significance to the satisfaction of employees' basic needs, the promotion of sustainable competitive advantages of organizations, and the construction of harmonious labor relations. Psychology of Working Theory uses decent work as the core variable to build a theoretical model, which has attracted the attention of scholars from all over the world. This article aims to report the results of a literature review of research concerning decent work. The study displays the antecedents and outcomes of decent work including mediators and moderators that have been tested. Also, the study categorize the theories, methods, and contexts of the reviewed studies. The study identifies the possible gaps and potential research directions. The findings can be helpful to further research in decent work as well as help managers understand this important concept.